Microbiota-regulated IL-25 increases eosinophil number to provide 1 protection during Clostridium difficile infection - Buonomo, Erica L. (Cell Rep, 2016)
Clostridium difficile infection (CDI) is the most common cause of hospital-acquired infection in the United States. Host susceptibility and the severity of infection are influenced by disruption of the microbiota and the immune response. However, how the microbiota regulates immune responses to mediate CDI outcome remains unclear. Here, we investigated the role of the microbiota-linked cytokine IL-25 during infection. Intestinal IL-25 was suppressed during CDI in humans and mice. Restoration of IL-25 reduced CDI-associated mortality and tissue pathology even though equivalent levels of C. difficile bacteria and toxin remained in the gut. IL-25 protection was mediated by gut eosinophils, as demonstrated by an increase in intestinal eosinophils and a loss of IL-25 protection upon eosinophil depletion. These findings support a mechanism whereby the induction of IL-25-mediated eosinophilia can reduce host mortality during active CDI. This work may provide targets for future development of microbial or immune-based therapies.